First, note that since sin(x) is between -1 and 1, and cos(y) is positive for y between -1 and 1, so cos(sin(x)) is positive for all x.
Next, consider the following:
D = {cos (sin x)}2 - {sin (cos x)}2
= 1 - {sin (sin x)}2 - {sin (cos x)}2.
Note that for all x, (sin x)2 <= [less than or equal to] x2, so
D >= 1 - (sin x)2 - (cos x)2 = 0.
Thus, since cos(sin x) > 0, this means
cos(sin x) >= sin(cos x) for all x.
Also, it follows that (sin x)2 = x2 only for x = 0, and
cos(sin 0) = 1 > sin(cos 0) ~ .8415
Therefore, cos(sin x) > sin(cos x) for all real x.